Organization and Application of ECLS Therapy—A Nationwide Survey in German Cardiosurgical Departments - Assmann, Alexander; Boeken, Udo; Klotz, Stefan; Harringer, Wolfgang; Beckmann, Andreas (The Thoracic and Cardiovascular Surgeon, 2019)
Background In context of the multidisciplinary German scientific guideline “Use of extracorporeal circulation (extracorporeal life support [ECLS]/extracorporeal membrane oxygenation) for cardiac and circulatory failure,” a nationwide survey should depict the status of organization and application of ECLS therapy in Germany.Methods Between June and October 2017, a standardized questionnaire consisting of 30 items related to ECLS therapy was sent to all German cardiosurgical departments, and all returned results were analyzed and evaluated.Results The return rate amounted to 92.9% (78 out of 84 departments). In the participating departments, ECLS therapy is subject to different responsibilities, and exhibits divergent processes and various ways for specialization of the involved personnel. This also concerns local application standards, such as cannulation strategies, anticoagulation management, left ventricular unloading, antiwatershed treatment, and weaning from circulatory support.Conclusion This nationwide survey underlines the necessity of a multidisciplinary guideline concerning ECLS therapy.
Keywords: cardiopulmonary bypass; extracorporeal life support; extracorporeal membrane oxygenation; cardiac and circulatory failure; statistics; survey